1214. The Effects of Modified Personal Protective Equipment (PPE) Protocols on Healthcare Personnel Providing Patient Care During the COVID-19 Pandemic: A Qualitative Assessment. (15th December 2022) - Chasco, Emily E; da Silva, Jaqueline Pereira; Jones, DeShauna; Dukes, Kimberly; Ward, Melissa; Herwaldt, Loreen
Abstract: Background: Healthcare personnel (HCP) faced personal protective equipment (PPE)-related challenges during the COVID-19 pandemic including supply shortages, additional PPE items, different designs, and modified protocols (PR)/guidelines. We used a human factors engineering- and ethnography-informed approach to qualitatively assess the effects of these challenges on HCP and their PPE use during the pandemic. Methods: We observed PPE use (e.g., donning/doffing) by HCP caring for patients with COVID-19, those under investigation (PUI), and those with other conditions in 1 acute, 1 intermediate, and 1 intensive care unit at a large Midwestern academic hospital. We conducted mini-interviews with a subset of HCP to clarify observed behavior and identify PPE-related concerns. We captured observation, interview, and additional data (e.g., unit layouts, signage) in structured and unstructured notes. We transcribed and imported notes into MAXQDA and applied a deductive-inductive analytical approach. Results: From April-July 2021, we observed 188 patient care episodes and conducted 47 mini-interviews. Observations included COVID-19 ( n =102), PUI ( n =4), and non-COVID-19 ( n =82) rooms on varying isolation precautions. PRs related to masks and eye protection changed during the study period and particularly affected donning practices. Other barriers included time-intensive PRs, unclear PR communication, unfamiliar designs, lack of surfaces on which to set supplies while donning/doffing, and inconvenient PPE storage/cleaning locations. We observed recommendation/PR deviations related to PPE use (e.g., exposed wrists, unapproved/no eye protection), cleaning, and signage/storage (e.g., designated "clean" surfaces). HCP reported PPE extended use/reuse, provision of design options, and their own adaptations (e.g., "batching" tasks, modifying PPE) facilitated donning/doffing. New PPE requirements highlighted tensions between HCP comfort and safety; despite this, some wanted to include modified PRs in their routine infection prevention practices permanently. Conclusion: PPE use barriers and facilitators related to modified COVID-19 PRs have implications for the ongoing pandemic and future respiratory pathogen outbreaks. Disclosures: Loreen Herwaldt, MD, 3M: 3M is providing products for one of Dr. Herwaldt's research studies unrelated to the work reported here.|PDI Healthcare: PDI Healthcare has provided research funding to Dr. Herwaldt unrelated to the work reported in this abstract.